2003
DOI: 10.1038/sj.npp.1300032
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Induces Glutamate Release from Thalamocortical Terminals in Prefrontal Cortex

Abstract: It has been proposed that activation of nicotinic acetylcholine receptors (nAChRs) can activate the prefrontal cortex, enhancing attention and cognition. Nicotine can stimulate the release of several different neurotransmitters in many brain regions. In the present study, we found that stimulation of nAChRs by nicotine or the endogenous agonist, acetylcholine (ACh), induces a large spontaneous increase in glutamate release onto layer V pyramidal neurons of the prefrontal cortex. This release of glutamate, meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
217
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(237 citation statements)
references
References 60 publications
19
217
1
Order By: Relevance
“…Increased presynaptic [Ca 2+ ]i likely underlies the nicotine-evoked release of neurotransmitter from cortical synaptosomes described previously to involve predominantly α7 nAChRs whose activation, in turn, triggers the opening of N-and P/Q-type VGCCs [25,26], though β2 nAChRs are likely involved as well [27,28]. In addition, increased presynaptic [Ca 2+ ]i also likely underlies nicotine enhancement of neurotransmitter release measured in cortical slices [29][30][31][32][33] and the intact cortex using microdialysis [19,34,35].…”
Section: Presynaptic Ca 2+ Responses Following Chronic Treatment Withmentioning
confidence: 83%
“…Increased presynaptic [Ca 2+ ]i likely underlies the nicotine-evoked release of neurotransmitter from cortical synaptosomes described previously to involve predominantly α7 nAChRs whose activation, in turn, triggers the opening of N-and P/Q-type VGCCs [25,26], though β2 nAChRs are likely involved as well [27,28]. In addition, increased presynaptic [Ca 2+ ]i also likely underlies nicotine enhancement of neurotransmitter release measured in cortical slices [29][30][31][32][33] and the intact cortex using microdialysis [19,34,35].…”
Section: Presynaptic Ca 2+ Responses Following Chronic Treatment Withmentioning
confidence: 83%
“…For example, in response to nicotine, glutamate release has been demonstrated in the prelimbic prefrontal cortex (Gioanni et al, 1999), and glutamate and aspartate release have been demonstrated in the VTA (Schilstrom et al, 2000). The finding of nAChR-induced glutamate release in the prefrontal cortex has also been demonstrated by measuring spontaneous excitatory postsynaptic currents (Lambe et al, 2003). Importantly, one of these studies (Gioanni et al, 1999) also demonstrated that nicotine administration facilitates thalamo-cortical neurotransmission through stimulation of nAChRs on glutamatergic neurons.…”
Section: Glutamatergic (And Other) Effects Of Nicotine/cigarette Smokingmentioning
confidence: 98%
“…The influence of nicotine on these symptoms has been greatly researched. Nicotine actively influences the increase in transmission of particular neurotransmitters in the brain (Avila et al, 2003;Gray et al, 1994;Jacobsen et al, 2004;Kumari and Postma, 2005;Lambe et al, 2003;Larrison-Faucher et al, 2004;Myers et al, 2004;Sacco et al, 2004;Sherr et al, 2002) and the reinforcing effects of nicotine are believed to result from its interaction with the mesocorticolimbic system. Others have suggested that nicotine enhances performance on cognitive tasks through an increase of the synaptic transmission of glutamate (Gray et al, 1996).…”
Section: Introductionmentioning
confidence: 99%